Cross-Listing and Stock Returns : Evidence from Nordic Equity Markets - Lampén, Nea (My University, 2026)
This thesis examines the stock market reactions to cross‑listing events among Nordic companies, focusing on both short‑term market responses and post‑listing stock performance. Previous research on cross‑listing has documented significant valuation effects in global markets, and evidence from highly developed and integrated Nordic capital markets remains relatively limited. The empirical analysis is based on a sample of 28 cross‑listing events involving Nordic companies from 1985 to 2026. An event‑study methodology is used to analyze short‑term market reactions around the listing date using cumulative abnormal returns (CAR) and buy‑and‑hold abnormal returns (BHAR). Long‑term performance is evaluated over a 120‑day period after the listing. The data for the study is obtained from the Bloomberg Terminal. Robustness checks using alternative benchmark models are employed to ensure that the results are not driven by model specification. The findings show that cross-listing events do not generate statistically significant abnormal returns at the aggregate level in either the short or long term. However, company-level analysis reveals notable heterogeneity among companies. Companies that cross-list on major international exchanges experience more favorable long-term outcomes than those that cross-list within the Nordic countries. The findings provide limited support for the bonding hypothesis and are more consistent with liquidity and market segmentation theories. The findings highlight the importance of market integration and company-specific characteristics in affecting cross-listing outcomes.

Tämä tutkielma tarkastelee osakemarkkinoiden reaktioita pohjoismaisten yritysten rinnakkaislistautumisiin (cross-listing), keskittyen lyhyen aikavälin markkinareaktioihin ja listautumisen jälkeiseen osakekurssikehitykseen. Aiempi kirjallisuus on osoittanut, että rinnakkaislistautumisilla voi olla merkittäviä yritykseen kohdistuvia arvostusvaikutuksia kansainvälisillä markkinoilla. Tutkimuksia korkeasti kehittyneistä ja integroituneista pohjoismaisista pääomamarkkinoista on kuitenkin suhteellisen vähän. Tutkielma perustuu 28 pohjoismaisen yrityksen rinnakkaislistautumistapahtumaan vuosina 1985–2026. Lyhyen aikavälin markkinareaktiota tarkastellaan tapahtumatutkimusmenetelmällä (event study), jossa hyödynnetään kumulatiivisia epänormaaleja tuottoja (CAR) ja ostaja‑ja‑pidä‑poikkeavia tuottoja (BHAR) listautumispäivän ympärillä. Pitkän aikavälin vaikutuksia tarkastellaan 120 päivän ajanjaksolla listautumisen jälkeen. Tutkimuksessa käytetty aineisto on kerätty Bloomberg‑tietokannasta. Tulosten luotettavuus varmistetaan herkkyysanalyyseillä, joissa hyödynnetään vaihtoehtoisia tuottojen vertailumalleja sen varmistamiseksi, ettei tulokset riipu mallivalinnasta. Tulokset osoittavat, etteivät rinnakkaislistautumistapahtumat aiheuta tilastollisesti merkitseviä poikkeavia tuottoja aggregaattitasolla, lyhyellä eikä pitkällä aikavälillä. Yrityskohtainen analyysi paljastaa kuitenkin huomattavaa vaihtelua yritysten välillä. Suuriin kansainvälisiin pörsseihin rinnakkaislistautuneet yritykset saavuttavat keskimäärin suotuisampia pitkän aikavälin tuottoja kuin yritykset, jotka ovat listautuneet ainoastaan pohjoismaisten pörssien välillä. Tulokset antavat rajallista tukea sitoutumishypoteesille (bonding hypothesis) ja ovat linjassa likviditeettiä ja markkinoiden segmentoitumista koskevien teorioiden kanssa. Tulokset korostavat markkinoiden integraation ja yrityskohtaisten tekijöiden merkitystä rinnakkaislistautumisen vaikutusten selittäjinä.
Keywords: capital market; stock prices; liquidity; valuation; investors; companies (business enterprises); stock exchanges; integration (passive); fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance